방사선사의 임금 적정성 및 직무 만족도 - 박재윤(Jae-Yoon Park); 강기봉(Gi-Bong Kang); 김규형(Gyoo-Hyung Kim); 안중성(Jung-Seong Ahn); 홍성완(Seong-Wan Hong); 이재석(Jae-Seok Lee); 권익수(Ick-Su Kwon); 최재호(Jae-Ho Choi) (방사선기술과학, 2018)
This study aims to provide the basic data helpful for the improvement of rights and interests of radiological technologists, by understanding the current working environment and if they get the proper reward through the analysis on the perception of appropriateness of current wage and job satisfaction of radiological technologists. Survey was conducted to evaluate the perception of satisfaction with job and wage system, work intensity, necessity of the radiological technologist limit system, and turnover in accordance. The appropriate starting salary was low in case of women and non-capital area, and when the age, academic background, career, and hospital size were lower. The appropriate wage was low in case of women and non-capital area, and when the academic background and hospital size were lower. The negative perception of the necessity to change the wage system was shown in university hospitals. Regarding the work intensity, in case of women and low career, and when the age, academic background, and hospital size were higher, the work intensity was perceived as high. When the academic degree and hospital size were lower, the positive perception of the radiological technologist limit was shown. The turnover intention was high in case of women, and when the age, academic background, career, and hospital size were lower. In order to increase the job satisfaction of radiological technologists, it would be necessary to the appropriate reward and the environment where they could concentrate on work.